Many skies : alternative histories of the sun, moon, planets, and stars - Upgren, Arthur R. (Rutgers University Press, 2005)
Many Skies: Alternative Histories of the Sun, Moon, Planets, and Stars examines the changes in science that alternative solar, stellar, and galactic arrangements would have brought, and explores the different theologies, astrologies, and methods of tracking time that would have developed to reflect them. Our perception of our surroundings, the number of gods we worship, the symbols we use in art and literature, even the way we form nations and empires are all closely tied to our particular (and accidental) placement in the universe. Upgren also explores the actual ways that human inte.